Integrating Universal Design for Learning Principles in Chemistry Education - Reeta Rai; Kezang Choden; Lhapchu Lhapchu; Sonam Rinchen (Journal of Research in Education and Pedagogy, 2025)
Universal Design for Learning (UDL) is a transformative educational framework for creating inclusive and equitable learning environments. Studies have documented its effectiveness in school chemistry education, particularly in improving accessibility and engagement. This study supported the understanding and application of UDL through a practice-based professional development programme for secondary school chemistry teachers teaching grades IX to XII using open educational resources (OERs) on atomic structure and organic chemistry, specifically designed in alignment with the principles of UDL. Teachers were given six weeks per module to engage with the content and apply UDL principles in their classrooms to improve instructional practices. The study investigated teachers’ understanding and application of UDL principles using pre-test and post-test assessments, lesson plan evaluations, classroom observations, and interviews. Test results showed that the intervention improved teachers’ UDL competencies, with remarkable gains in content representation in both the modules and student engagement through multiple strategies in atomic structure. However, the improvement in engaging students through multiple strategies during organic chemistry lessons and the use of multiple assessment methods across both modules was smaller, indicating a need for additional support in these areas. Lesson plans and reflection reports showed high proficiency in content representation and student engagement in both modules, and creating multiple means of expression in organic chemistry, but moderate proficiency in creating diverse opportunities for expression in the atomic structure module. This study emphasises the effectiveness of integrating UDL-based OERs into professional development initiatives for secondary school chemistry teachers. Such integration not only strengthens teachers’ instructional practices but also contributes to building more inclusive classrooms that accommodate diverse learners’ needs. Accordingly, this study recommends supporting teachers’ professional development programmes using UDL-based OERs to enhance their instructional practices and inclusive and equitable learning environments in chemistry education and beyond.